Recommendations of the ESSR Arthritis Subcommittee on Ultrasonography in Inflammatory Joint Disease - Plagou, Athena; Teh, James; Grainger, Andrew J.; Schueller-Weidekamm, Claudia; Sudoł-Szopińska, Iwona; Rennie, Winston; Åström, Gunnar; Feydy, Antoine; Giraudo, Chiara; Guerini, Henri; Guglielmi, Giuseppe; Isaac, Amanda; Jans, Lennart; Jurik, Anne Grethe; Kainberger, Franz; Maas, Mario; Martinoli, Carlo; Mascarenhas, Vasco V.; Miese, Falk; O'Connor, Philip; Oei, Edwin H.; Østergaard, Mikkel; Peetrons, Philippe; Platzgummer, Hannes; Reijnierse, Monique; Robinson, Philip; Rupreht, Mitja; Simoni, Paolo; Wick, Marius C.; Zejden, Anna; Klauser, Andrea S. (Seminars in Musculoskeletal Radiology, 2016)
This article presents the recommendations of the European Society of Musculoskeletal Radiology Arthritis Subcommittee on the use of ultrasonography (US) in rheumatic disease, focused on the examination of joints in the adult population. The recommended examination technique and protocols used in a radiologic work-up are discussed. The main US features that can lead to a final diagnosis in the most common rheumatic diseases are addressed. The differential diagnosis that should be considered at image interpretation is presented. The role of US in interventional procedures and clinically important recent developments is also discussed.
Keywords: ultrasound; inflammatory joint disease; arthritis; ESSR